Implementation of Simple Additive Weighting to Determine Priority for Handling Customer Complaints - Yuwan Jumaryadi; Tedjo Nugroho (IJISTECH (International Journal of Information System and Technology), 2021)
The number of population is increasing, and the competition is getting tougher. It requires companies to remain able to survive and be able to compete with other companies, especially with companies that have the same line of business. The increasing use of the internet today has caused many changes in various fields. Many efforts are made by the company to survive, including by providing the best service to its customers. The use of existing technology for developing information systems for handling customer complaints is expected to help companies improve the quality of their products or services. In company management, it is important to provide good quality service in order to increase customer satisfaction. By determining the priority for handling customer complaints, it is expected to improve the Key Performance Indicator (KPI) of engineers. The decision-making process using the simple additive weighting method is carried out by weighting each criterion. This research is expected to determine the priority of handling customer complaints so that it can help engineers in determining the priorities for handling existing complaints.